ANALYSIS OF THE RESULTS OF CADASTRAL EVALUATION OF BUILDINGS, PREMISES, CONSTRUCTION IN TRANSPORT TECHNOLOGY - V. Osennyaya, A.; A. Hahuk, B.; A. Gura, D.; I. Khusht, N.; Ch. Kuadze, E; A. Kushu, A. (Gênero & Direito, 2020)
This article is devoted to the study of the results of the cadastral valuation of buildings, premises, construction in progress and parking lots, which was carried out in 2018 in the Krasnodar Territory [7]. The shortcomings of the structure of the presentation of the approved results of the cadastral assessment were identified and analyzed, a new form of entering and sorting data was proposed to simplify the work with them.